HEALTHCARE SPENDING EFFICIENCY IN RUSSIAN REGIONS - N. A. Avxentyev; V. M. Baydin; O. A. Zarubina; N. N. Sisigina; S. A. Kulkova (Фармакоэкономика, 2016)
Life expectancy to healthcare spending ratio differs significantly among the Russian regions. The differences could be explained with both non-discretionary factors and the regional management efficiency. The main aim of this article is to evaluate the efficiency of the regional healthcare in Russia employing the formal methodological approach. We use three-step data envelopment analysis (DEA) in order to (1) calculate the technical efficiency scores for regional healthcare systems, (2) determine non-discretionary factors affecting the scores and (3) exclude the non-discretionary component from scores to asses the management efficiency. Using data for 76 Russian regions in 2006-2013 we found approx. 27% regional healthcare spending inefficient, which equals to real 269-435 billion rubles of inefficient spending annually.